Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) (x2 - 2x - 1)(x - 3)
= x2(x - 3) - 2x(x - 3) - 1(x - 3)
= x3 - 3x2 - 2x2 + 6x - x + 3
= x3 - 5x2 + 5x + 3
2. (-x + 4)(-x2 + 4x - 1)
= -x(-x2 + 4x - 1) + 4(-x2 + 4x - 1)
= x3 - 4x2 + x - 4x2 + 16x - 4
= x3 - 8x2 + 17x - 4
3 ) (2x - 1)(x2 - 5x + 3)
= 2x(x2 - 5x + 3) - 1(x2 - 5x + 3)
= 2x3 - 10x2 + 6x - x2 + 5x - 3
= 2x3 - 11x2 + 11x - 3
Bài làm :
1) (x2 - 2x - 1)(x - 3)
= x2(x - 3) - 2x(x - 3) - 1(x - 3)
= x3 - 3x2 - 2x2 + 6x - x + 3
= x3 - 5x2 + 5x + 3
2) (-x + 4)(-x2 + 4x - 1)
= -x(-x2 + 4x - 1) + 4(-x2 + 4x - 1)
= x3 - 4x2 + x - 4x2 + 16x - 4
= x3 - 8x2 + 17x - 4
3 ) (2x - 1)(x2 - 5x + 3)
= 2x(x2 - 5x + 3) - 1(x2 - 5x + 3)
= 2x3 - 10x2 + 6x - x2 + 5x - 3
= 2x3 - 11x2 + 11x - 3
a, \(\left(2x^3-x^2+5x\right):x=2x^2-x+5\)
b, \(\left(3x^4-2x^3+x^2\right):\left(-2x\right)=-\frac{3}{2}x^3+x^2-\frac{1}{2}x\)
\(\left(2x^3-x^2+5x\right):5=\left(2x^3:x\right)+\left(-x^2:x\right)+\left(5x:x\right)=2x^2-x+5\)
\(\left(3x^4-2x^3+x^2\right):\left(-2x\right)=[3x^4:\left(-2x\right)]+[-2x^3:\left(-2x\right)]+[x^2:\left(-2x\right)]=-\frac{3}{2}x^3+x^2-\frac{x}{2}\)
\(2x\left(x+3\right)-x\left(2x-1\right)\)
\(=2x^2+6x-2x^2+x\)
\(=7x\)
\(2x\left(x+3\right)-x\left(2x-1\right)\)
\(=2x^2+6x-2x^2+x=7x\)